Do Predictors of Health Facility Delivery Among Reproductive-Age Women Differ by Health Insurance Enrollment? A Multi-Level Analysis of Nigeria's Data - Zhang, Xiaomei; Anser, Muhammad Khalid; Ahuru, Rolle Remi; Zhang, Zizai; Peng, Michael Yao-Ping; Osabohien, Romanus; Mirza, Mumal (Frontiers in Public Health, 2022)
The aim of the study was to compare determinants of health facility delivery for women under health insurance scheme and those not under health insurance scheme. Secondary data drawn from the most recent National Demographic and Health Survey (2018) was used for the analysis. The characteristics of the women were presented with simple proportion. Binary multilevel logistic regression was used to examine the determinants of health facility for women who enrolled in health insurance and those who do not. The result showed that 2.1 % of the women were under health insurance scheme. The unique determinants of health facility for women under health insurance were parity and birth order, while unique determinants of health facility delivery for women not enrolled in health scheme were employment status, marriage type and geopolitical zones. Uniform predictors of health facility delivery for both groups of women were maternal education, household wealth quintiles, autonomy on healthcare, number of antenatal contacts, residential status, community-level poverty, community-level media use and community-level literacy.